The American side [videorecording (DVD)] - Stuhr, Greg; Stuhr, Greg; Ricker, Jenna; Bachleda-Curus, Alicja; Belle, Camilla, 1986-; Broderick, Matthew, 1962-; Forster, Robert, 1942-2019-; Garofalo, Janeane (Sony Pictures Home Entertainment, 2016)
Following a mysterious suicide at Niagara Falls, a low-rent detective unravels a conspiracy to build a revolutionary invention by enigmatic scientist, Nikola Tesla.